UJI EFEKTIVITAS ANTIDIABETIK FRAKSI EKSTRAK DAUN GALING (Cayratia trifolia L. Domin.) PADA MENCIT JANTAN BALB/C YANG DIINDUKSI STREPTOZOTOCIN (STZ) - Muhammad Ilyas Y; Fadhliyah Malik; Nuralifah; Karmilah; Irma (Sekolah Tinggi Ilmu Kesehatan Borneo Lestari Banjarbaru, 2019)
ABSTRACT Diabetes Mellitus (DM) was a disease or disorder of chronic metabolism which be characterized by high blood sugar levels along with carbohydrate, lipid, and protein metabolism disorders as a result of insulin function insufficiency. Treatment of diabetes could be overcome by utilizing nutritious plants, one of which was thegaling leaves (Cayratia trifolia L. Domin.). The galing plant contained secondary metabolites such as alkaloids, phytosterol saponins, phenols, flavonoids and tannins. Flavonoids were suspected as an antidiabetic agent. This study aimed to determine the effectiveness of some fractions of galing leaves extract in lowering blood glucose levels at mice which be induced streptozotocin (STZ). The research design used was a completely randomized design consisting of five treatment groups consisting of positive control (glibenclamide 5 mg) and negative control (Na. CMC 0,5%) with three replications. The results showed that there were significant differences in each treatment group (Fhit> Ftabel 0.05) of the antidiabetic effect, where ethyl acetate fraction had the best effectiveness in reducing blood glucose levels in Balb / C male mice that were STZ induced when compared with positive control of glibeklamid. Keywords : Antidiabetic, Cayratia trifolia L. Domin, Fraction, Blood glucose, STZ, mice Balb/C